ALTERNATIF PENANGANAN FUNGSI KEBERSIHAN UMUM DI KABUPATEN ASAHAN KASUS KOTIF KISARAN DAN 6 IKK UTAMA - Sofian
Abstract : The District of Asahan has a population of 912,000 with 169,000 of people living in the town. At present, the District of Asahan is facing an increasing demand on its sanitations services and more particulary the problem of garbage disposal. This problem is occuring mainly in the administrative Town of Kisaran and main sub-district capitals. The problem now facing these towns is due to a number of factors: the increase in population and the corresponding increase in demand for sanitations services, especially garbage, the low level of awareness of society in the problem of garbage disposal, the increase in the amount of unhauled garbage which is currently being produced at rate of 180 mi/day in Kotif Kisaran and 90 m3/day in the main sub-district capitals and an increase in the financial burden of the Regional Government of Asahan due to the increasing demand on sanitation services. Some of the main problem associated with this increase in demand include: lack of garbage handling facilities in the towns, inadequate funds for the Regional Government of Asahan to provide facilities, the community and private enterprise have not actively participated in the disposal of garbage and the management of this is left to the Regional Government of Asahan. With its limited resources, the Regional Government of Asahan has tried to increase the capasity of its garbage handling facilities without increasing the burden to the APBD of the Regional Government of Asahan. Infact, it is hoped that garbage disposal activity could become a revenue point for the Government. In line with this, this thesis is aimed at trying to find solutions to the problem of garbage disposal in the Asahan Region. The research covered in this thesis has tried to answer a research issue composed of the following questions: 1) What alternatives are there in the disposal of garbage in Kotif Kisaran and in the following sub-district capitals: Kota Pangkalan Dodek, Indrapura, Lima Puluh, Tanjung Tiram, Binjei Serbangan and Bagan Asahan? 2) What is the role of the Regional Government of Asahan, its citizens and private enterprise in the disposal of garbage? 3) What steps are needed to fulfil these goals? Given this background of the problems associated with sanitary services in general and garbage handling in particular, the essential problem facing this research is to find financially viable solutions within the limited resources available to the people and the governments of this towns. In judging the usefulness of this research, consideration must be given to its practical input into the effort of the Regional Government of Asahan to implement garbage handling facilities, especially in the towns. In responding to this problem, the methodology used in this thesis include literature study, primary survey examining people\'s ability to pay for services in the locations given, secondary data from collection services and orther bodies in the region of Asahan and its sub-districts. Seven alternatives of garbage disposal have been put forward. In determining the value of any particular alternative, the basic tool used was Internal Rate of Return (IRR) analysis. The result of this analysis is as follows: 1) In the area of Kotif Kisaran, three alternatives of garbage handling were examined indicating that one alternative resulted in an IRR of 17.70%. This was based on retribution Rp.4,000 per month per household in the town centre and Rp.2,000 per month per household in the residential areas of the town and on the condition that the number of subcribers increased at the rate of 7.72% per year and that retribution increased by 10% per 5 years. This indicates that garbage handling in Kotif Kisaran is able to stand alone as an investment especially when compared to the current interesrt rate of 14%-15% per year. 2) Three alternatives were analised in connection with the 6 main IKKS:an average retribution c-ha e-Rp.1,000 per month per household, Rp.2,000 per month per household in the centre of town and Rp.1, 000 per month per hausehold in the residential areas, Rp.2,500 per month per hosehold and Rp.1, 000 per month per household in the residential areas. The following criteria were applied: that the number of subcribers will increase by 2% per year and retributions increased by 10% per 5 years. Analysis of these alternatives indicates that cash flows would be negative. This means that garbage handling in the 6 main IKKs are unable to stand alone as an investment.and have to be subsidized by the Regional Government of Asahan. 3) For combined garbage handling between Kotif Kisaran and 6 main IKKs, one alternative has been examined under the following criteria: Retributions by each household in Kotif Kisaran is Rp.4,000 per month in the town centre and Rp.2,000 per month in the residential areas around town. In 6 main IKKs, the rate would be Rp.2,500 per month in the town centre and Rp.l, 000 per month in the residential areas around town. Some orther criteria are matched with the criteria used in each town. The IRR value of this alternative is 6.92%. This indicates that although Kotif Kisaran is able to stand alone as a viable investment, however, it is still insufficient to subsidize the 6 main IKKs. It also indicates that the 6 main IKKs would still have to be subsidized by the Regional Government of Asahan. Conclusions from this analysis show garbage handling in Kotif Kisaran is able to stand alone as a viable investment, however, it is still insufficient to subsidize the 6 main IKKs listed above and so they would need to be subsidized by the Regional Government of Asahan. Further, in order to lessen the financial burden on the Regional Government of Asahan, particularly in the area of garbage handling and to increase the sanitation services available to the society with private enterprise offered the chance of involvement and to increase the participation of the people, it is recomended that garbage handling in Kotif Kisaran is handed over to private enterprise. This takes into account that the IRR 17.70%. Some discretionary steps which have been suggested include that sanitary handling in Kotif Kisaran is introduced as soon as possible before Kotif Kisaran becomes a municipality. It is also suggested that garbage handling in Kotif Kisaran is performed by private enterprise, the facilities owned for so long by Kotif Kisaran are returned to The Regional Government of Asahan and further, handed over to the sanitary services to handle garbage disposal in the 6 main IKKs. Public perception also needs to be changed so that society has better understanding of the importance of proper waste disposal and that waste disposal is not the responbility of the Government alone but of all parties. It is also suggested that information is made available to citizens and private parties about those activities which have so far been performed by the Regional Government of Asahan but which are now performed by enterprise. It is also recommended that, in handling over garbage disposal service to private enterprise, a monopolistic system is avoided and competition is encouraged.